ANALYSIS OF BRAND STRATEGY, STRATEGY OF MARKETING, AND MARKETING MIX AT NOORE SPORT HIJAB IN ENTERING THE INTERNATIONAL MARKET - Khoirunisa Aryni Putri; Mohammad Zaenal Abidin (University of Darussalam Gontor, 2020)
The purpose of this study is to analyze the brand strategy, strategy of marketing, marketing mix, and international market entry strategy implemented by Noore Sport Hijab. The method used in this research is descriptive with a qualitative approach. Data collection techniques in this study used interviews, observation, and documentation. The results of this study indicate that Noore Sport Hijab positions its brand as the modest active wear. The most dominant brand identity is color. Elastic is the brand personality of Noore Sport Hijab. Noore Sport Hijab communicates its brand through #HijabFofTheChampion. Noore Sport Hijab classifies its market segments based on demographics and psychography. The target market is Muslim women who are active in sports. Noore Sport Hijab positions its product as a solution for active Muslim women. The Product Strategy used is the Focused Strategy. The Price Strategy used is the Penetration Pricing Strategy. The place strategy used is the Exclusive Distribution Strategy. Promotion Strategy used in the form of Advertising, Publicity, and Sales Promotion. Noore Sport Hijab uses an export strategy in entering the international market. The Export Strategy used is the Indirect Export Strategy. As for the destination countries of Noore Sport Hijab in exporting include: Singapore, Malaysia, Brunei, United Arab Emirates, United Kingdom, Germany, France, Russia, United States of America, Canada.